Motivasi kerja islam dalam memediasi hubungan human relation dan beban kerja terhadap kinerja karyawan PT. Metinca Prima Industrial Works Salatiga - Rahayu, Septyana; Pratama, Abdul Aziz Nugraha (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
This research aims to analyze and determine the influence of human relations and workload on employee performance, mediated by Islamic work motivation. The method used in this research is quantitative, with primary data obtained from the results of questionnaires distributed and filled in by PT employees. Metinca Prima Industrial Works Salatiga is as many as 118. The data analysis techniques used are path analysis and the Sobel test. The research results show that human relations and Islamic work motivation have a positive and significant effect on performance, while workload has an insignificant positive effect. Workload and human relations positively and significantly affect Islamic work motivation. Islamic work motivation cannot mediate the relationship between human relations and workload on performance.